Budget Governance Factors: A Survey of Lecturers at Private Universities in the South Sumatra Region - Muhammad Helmi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
This study aims to determine the factors that influence budget governance. The verification research method uses to answer the formulation of a predetermined problem. Respondents who sampled were 103 permanent lecturers of private universities in the South Sumatra region. The results showed that all the proposed hypotheses proved significant. The results showed that the increased ease of obtaining a budget and simple budget administration expected to increase the Budget Governance variable.